The multibody systems approach to vehicle dynamics - Blundell, Michael; Harty, Damian (Butterworth-Heinemann, 2015)
Filling the gaps between subjective vehicle assessment, classical vehicle dynamics and computer-based multibody approaches, this book offers coverage of both the virtual and practical aspects of vehicle dynamics from concept design to system analysis and handling development. It provides foundation knowledge of vehicle dynamics as well as drawing on laboratory studies, test-track work, and finished vehicle applications to gel theory with practical examples and observations. Combined with insights into the capabilities and limitations of multibody simulation, this comprehensive mix provides the background understanding, practical reality and simulation know-how needed to make and interpret useful models. Topics include: coverage of the latest tire models; changes to the modeling of light commercial vehicles; developments in active safety systems; torque vectoring; and examples in AView; as well as updates to theory, simulation, and modeling techniques. --